On a method for inverse theorems for (C,1) and gap (C,1) summability - Vojislav Maric; Miodrag Tomic (International Journal of Mathematics and Mathematical Sciences)
A simple method for proving several theorems of Tauberian and Mercerian type for (C,1) and gap (C,1) summability is presented.